ANALISIS SOSIAL EKONOMI PERANAN PEREMPUAN PEDESAAN DI DALAM KELUARGA DAN MASYARAKAT - Dina Novia Priminingtyas (Universitas Tribhuwana Tunggadewi, 2007)
This an explanatory research was aimed to describe roles of rural women eithin family and society at Mangunrejo village of Kepanjen District, Malang Regency. The Multiple Linear Regression Analysis showed that education and working time strongly vorrelated to. women’s income. Averages of women’s income contributed to 48,22% and single mother was able to gain 100%. It means that women’s income is not only secondary income but also primary income. Family has held importance key role to defence social stability, include women’s role in family, career and social activity. Women have to adaptate with their social environment to carry out their roles in family and social community to raise the family’s capital. Women’s roles are able to integrate to their hearth and behavior